Influence of lipid extraction methods as pre-treatment of microalgal biomass for biogas production - Neves, Viviane T. de C.; Sales, Emerson Andrade; Perelo, Louisa W. (Renewable & sustainable energy reviews, 2016)
One of the important issues concerning anaerobic digestion of microalgal biomass is the influence of the pretreatment on methane production. Various techniques can be used to extract lipids from microalgae, including thermal, chemical or physical processes. The process of lipid extraction can be considered as a pretreatment. Given the economic and ecologic importance of the integration of anaerobic digestion in the microalgae biodiesel production process, this article aims to review the literature about this subject, and relates the influence of various forms of lipids extraction on the methane generation by anaerobic digestion of residual microalgae biomass. The oil extraction using chloroform as a solvent should not be performed if the residue is to be exploited for anaerobic digestion, due to the inhibiting character of this solvent on methanogenic activity. The lipid extracted microalgal biomass presents higher methane yield compared to the raw microalgal biomass with few exceptions. The thermochemical method is the most commonly used pretreatment for lipid extraction of microalgal biomass. Nevertheless, research using pretreatment methods that require less energy such as mechanical and biological should be stimulated. Thus, the energy balance may become more favorable with the use of residual microalgae biomass as an energy source.